2009
DOI: 10.1002/micr.20661
|View full text |Cite
|
Sign up to set email alerts
|

Is the recipient vein really the main concern? A cohort study of head and neck reconstruction

Abstract: The aim of this study was to verify the role of the venous drainage system in the pathogenesis of complications in microsurgical head and neck reconstruction. In a nonrandomized cohort study, 52 consecutive cases of complex head and neck microsurgical reconstruction were evaluated. The patients were divided in two groups based on the treatment: the deep (DVDG; n = 30) and superficial (SVDG; n = 22) venous drainage groups. The complications evaluated included vascular obstruction with partial or total loss of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Eleven articles on microvascular procedures suggested an association between smoking and perioperative complications (Table III), [26][27][28][29][30][31][32][33][34][35][36] whereas six did not (Table IV). [37][38][39][40][41][42] Four articles showed mixed results, meaning that some analyses showed increased complications related to tobacco and some did not (Tables III and IV). [43][44][45][46] In addition, one article by Moore and colleagues evaluated the effects of smoking on regional head and neck reconstruction via cervicofacial and cervicothoracic rotation flaps after oncologic resection.…”
Section: Extirpative Surgerymentioning
confidence: 99%
“…Eleven articles on microvascular procedures suggested an association between smoking and perioperative complications (Table III), [26][27][28][29][30][31][32][33][34][35][36] whereas six did not (Table IV). [37][38][39][40][41][42] Four articles showed mixed results, meaning that some analyses showed increased complications related to tobacco and some did not (Tables III and IV). [43][44][45][46] In addition, one article by Moore and colleagues evaluated the effects of smoking on regional head and neck reconstruction via cervicofacial and cervicothoracic rotation flaps after oncologic resection.…”
Section: Extirpative Surgerymentioning
confidence: 99%
“…The strategic location of the IJV makes it an important anatomical landmark for ND [ 3 ]. Moreover, in H&N operations involving reconstruction with free flaps, the IJV and its tributaries provide the recipient veins used for microvascular anastomosis [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the IJV is further heightened in H&N cancer cases that require reconstruction with free tissue transfer as the IJV itself (end-to-side anastomosis) or its tributaries (end-to-end anastomosis) are the most common recipient vessels for the venous anastomosis of the free flap [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 Most authors reported that each system is equally reliable, 4,[15][16][17][18] while other studies supported that IJVS is the ideal recipient if technically feasible. [19][20][21] Although debates over which system is more adequate are currently in progress (summarized in ►Table 3), each system has its own advantages and disadvantages. The IJVS provides a wide range of choices with its multiple branches and has merits in facilitating venous flow by negative intrathoracic pressure during inspiration.…”
Section: Discussionmentioning
confidence: 99%